Meta-Analisis Kualitatif Bahan Ajar Tematik Tipe Webbed Tahun Ajaran 2020/2021 - Lintang Febriliani Cahya A; Eunice Widyanti Setyaningtyas (Peneliti.net, 2021)
The background of this research is that teaching materials are used as a way to determine the effectiveness of developing webbed-type teaching materials. Development of teaching materials as an understanding of learning design. Furthermore, the development of teaching materials must consider the teaching materials to be developed. Teaching materials must have a flexible nature, which means they can accept new things that have not been included in the content of the lesson during implementation. There are a number of reasons why teachers need to develop teaching materials, including; availability of materials according to curriculum demands, target characteristics, and learning problem solving demands. The development of teaching materials must pay attention to the demands of the curriculum, meaning that the learning materials that we will develop must be in accordance with the curriculum. At the education unit level curriculum, graduate competency standards have been set by the government, but how to achieve it and what teaching materials are used is left entirely to educators as professionals. In this case, teachers are required to have the ability to develop their own teaching materials. To support the curriculum, a teaching material may occupy a position as a main or supplementary teaching material. The main teaching materials are teaching materials that meet the demands of the curriculum. While supplementary teaching materials are teaching materials intended to enrich, add to or deepen the content of the curriculum. Research Results Qualitative meta-analysis, namely the development of webbed-type teaching materials is very interesting for students' learning, so that it has a positive impact on student posttest results at the elementary and junior high school levels.